Технологічні напрямки щодо забезпечення якісного виготовлення крупногабаритних редукторів - Ковальов, Віктор Дмитрович; Васильченко, Яна Василівна; Антонюк, Віктор Степанович; Волошин, Олексій Іванович; Рябченко, Сергій Васильович (НТУ "ХПІ", 2017)
Плідність роботи полягає в тому, що результати по забезпеченню якісного виготовлення крупногоабарітних редукторів знаходяться на рівні світових аналогів. Розроблені нові технологічні напрямки в виготовленні крупногабаритних редукторів з використанням нових вид зубчастих зачеплень з гарантованим рідинним змащуванням зони контакту, нові інноваційні технології виготовлення зубчастих коліс з гідродинамічними карманами для утворення рідинного режиму змащування в зоні контакту. Внаслідок цього забезпечується зниження коефіцієнта тертя, контакт здійснюється через мастильний шар рiдини, яка знаходиться на момент утворення контакту в неньютоновському стані рідини завдяки гідрокарманам з утворенням пружно-нестислової мастильної рідини. Гідрокармани на евольвентній поверхні ведучого циліндричного зубчастого колеса зубчастої циліндричної передачі забезпечують високу несучу здатність конактуємих евольвентних поверхонь.

The article describes the results of the work to ensure the quality production of large-size gearboxes. Based on the use of modern technology in ma-chine building and the generalization of scientific achievements in the gearshift of hardened coarse-grained cogwheels and the requirements for heavi-ly loaded and critical gears, the general principles for the development of new innovative technologies and schemes for shaping gears using the mod-ern capabilities of numerical software Management and development of new machine tools. This provides an improvement in the quality and accura-cy of cogwheels up to 12 m in diameter, a module up to 65 mm and processing capacity 3-6 times. New technological directions for the manufacture of large-sized gearboxes using new types of gearing with guaranteed liquid lubrication of the contact zone, new innovative technologies for manufac-turing gears with hydrodynamic pockets for the formation of a liquid lubrication regime in the contact zone have been developed. Hydrokams on the involute surface of the leading cylindrical gear wheel provide a high load-bearing capacity of the curable involute surfaces. Such gear cylindrical gears provide high damping of pulsating load of gears of large-sized reducers, allow to reduce a technological heredity of errors of processing of the interfaced surfaces of cogwheels and reducer housings.
Technological directions for providing high-quality production of large-size reducers
Keywords: важке машинобудування; різець; передній кут; кут підйому нарізі; половинний кут; кут нахилу; статичний передній кут; замкова нарізь; dragline Heavy engineering; innovative technologies; large-size reduction gears; new kind of gearing; damping; pulsating load; improving quality; accuracy; productivity